Evolution of determinant factors of repeated sprint ability - Pareja-Blanco, F.; Suarez-Arrones, L.; Rodriguez-Rosell, D.; Lopez-Segovia, M.; Jimenez-Reyes, P.; Bachero-Mena, B.; Gonzalez-Badillo, J. J. (Journal of Human Kinetics, 2016)
The aim of this study was to investigate the changes in the relationships between repeated sprint ability (RSA) and anthropometric measures as well as fitness qualities in soccer players. Twenty-one professional soccer players performed several anthropometric and physical tests including countermovement vertical jumps (CMJs), a straight-line 30 m sprint (T30), an RSA test (6 x 20 + 20 m with 20 s recovery), a progressive isoinertial loading test in a full squat, a Yo-Yo Intermittent Recovery Test Level-1 (YYIRT-1) and a 20 m shuttle run test (20mSRT). The mean (RSAmean), the fastest (RSAbest), each single sprint time, and the percentage in a sprint decrease (%Dec) in the RSA test were calculated. RSAbest correlated significantly with RSAmean (r = .82) and with all single sprints (p < 0.05), showing a downward trend as the number of sprints performed increased. No significant relationship was observed between the %Dec and RSA performance. CMJs and the T30 also showed a correlation with RSA performance, whereas lower limb strength did not show any relationship with RSA performance. RSAmean showed significant (p < 0.05) relationships with body mass (r = .44), adiposity (r = .59) and the YYIRT-1 (r = -.62), increasing as the number of repeated sprints increased. The 20mSRT showed minimal relationships with RSA performance. In conclusion, maximal sprint capacity seems to be relevant for the RSA performance, mainly in the first sprints. However, high intermittent endurance capacity and low adiposity might help enhance the RSA performance when increasing the number of repeated sprints.